Hypoxia converts the myogenic action of insulin-like growth factors into mitogenic action by differentially regulating multiple signaling pathways - Ren, H.; Accili, D.; Duan, C. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Insulin-like growth factors (IGFs) stimulate myoblast proliferation and differentiation. It remains elusive how these mutually exclusive cellular responses are elicited by the same growth factor. Here we report that whereas IGF promotes myoblast differentiation under normoxia, it stimulates proliferation under hypoxia. Hypoxia activates the HIF-1 transcriptional program and knockdown of HIF-1 changes the mitogenic action of IGF into myogenic action under hypoxia. Conversely, overexpression of HIF-1? abolishes the myogenic effect of IGF under normoxia. Under normoxia, IGF activates the Akt-mTOR, p38, and Erk1/2 MAPK pathways. Hypoxia suppresses basal and IGF-induced Akt-mTOR and p38 activity, whereas it enhances and prolongs IGF-induced Erk1/2 activation in a HIF-1-dependent fashion. Activation of Akt-mTOR and p38 promotes myogenesis, and p38 also inhibits proliferation. Activation of Erk stimulates myoblast proliferation but inhibits differentiation. These results suggest that hypoxia converts the myogenic action of IGFs into mitogenic action by differentially regulating multiple signaling pathways via HIF-1-dependent mechanisms. Our findings provide a mechanistic explanation for the paradoxical actions of IGFs during myogenesis and reveal a novel mechanism by which cells sense and integrate growth factor signals and oxygen availability in their microenvironments.